The metastatic site does not influence PD-L1 expression in advanced non-small cell lung carcinoma. (June 2019) - Wang, H.; Agulnik, J.; Kasymjanova, G.; Fiset, P.O.; Camilleri-Broet, S.; Redpath, M.; Cohen, V.; Small, D.; Pepe, C.; Sakr, L.; Spatz, A.
Highlights: The PD-L1 expression similar in NSCLC from distant metastatic sites. Samples from any accessible distant metastatic sites can be used for PD-L1 testing. The discrepancy of PD-L1 between two metastatic sites likely due to heterogeneity. Abstract: Introduction: PD-L1 expression by immunohistochemistry (IHC) testing with Tumor Proportion Score (TPS)≥ 50% and≥ 1% is required to be eligible for first- and second-line Pembrolizumab treatment for metastatic non-small cell lung cancer (NSCLC) respectively. Stage IV NSCLC often presents with metastasis to multiple distant sites which are easily accessible for biopsy. Knowing whether PD-L1 IHC TPS can be indifferently measured from different metastatic site is therefore an important clinical question. In this study, we evaluated PD-L1 expression in NSCLC from varied distant metastatic sites. Methods: A total of 580 NSCLC specimens of distant metastases were retrieved for study, including 35 paired samples from two different metastatic sites. The metastatic sites included brain, bone, remote lymph nodes, serous membranes (pleura, pericardium and peritoneum), extra-thoracic solid organs and skin/soft tissues. The samples were cytology cell blocks, small biopsies or surgical resections. IHC was performed using Dako PD-L1 IHC 22C3 pharmDx. A total of 100 viable tumor cells was required for adequacy. TPS ≥ 50% and 1–49% were defined as high and low PD-L1 expression respectively. Results: PD-L1 TPS scores were not significantly different across a range of distant metastatic sites nor between metastases in paired samples. Conclusion: Our results suggest that the PD-L1 TPS scoring is similar across different metastatic sites and any site biopsied will yield necessary information for guiding clinical management.